Hydrogen production from municipal waste and low grade lignite blend - Muhammad Mueed Khan; Abdul Basit Amjad (Results in Engineering)
The updraft rotating bed gasifier (URBG) offers a sustainable solution for waste-to-energy conversion, utilizing low-grade lignite and municipal solid waste (MSW) from metropolitan dumping sites. This study investigates the co-gasification of lignite with various MSW components, demonstrating a significant enhancement in gasification efficiency due to the synergistic effects arising from their higher hydrogen-to-carbon (H/C) ratios. We find feedstock blending is key to maximizing gasification efficiency from 11% to 52% while reducing SOx emissions from 739 mg/kg to 155 mg/kg. Increasing the combustion zone temperature to 1100 K resulted in a peak hydrogen yield which was 19% higher than at 800 K. However, steam management is complicated as increasing it improves hydrogen fraction in produced gas but gasification efficiency is compromised. These findings showcase the URBG's potential to address both energy production and waste management challenges, guiding fossil-reliant regions toward a more sustainable energy future.